2019
DOI: 10.14258/abs.v5.i1.5209
|View full text |Cite
|
Sign up to set email alerts
|

Infraspecific morphological variations of Salvia limbata in Iran

Abstract: Salvia limbata is an aromatic herb of Lamiaceae, which distributed in different parts of Iran. Studies have revealed that this species has several benefit compounds for human health. In this study, we investigated infra‒specific morphological difference in this species. In total, 21 inflorescence morphological features were evaluated in eight populations; ten individuals were evaluated per each population. Data were analysed using SPSS and MVSP softwares. Morphological traits highly differed among the studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Leigh & Bryant 2015) revealed that haplotype network (Popart analysis) is performed in the analysis of population genetic data to visualize genealogical relationships at the infraspecific level, and to make inference about population's biogeography and history. Talebi et al (2019b) investigated morphological characteristics of eight populations of this species. They reported high morphological variations among the populations, and these populations were divided into four distinct groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leigh & Bryant 2015) revealed that haplotype network (Popart analysis) is performed in the analysis of population genetic data to visualize genealogical relationships at the infraspecific level, and to make inference about population's biogeography and history. Talebi et al (2019b) investigated morphological characteristics of eight populations of this species. They reported high morphological variations among the populations, and these populations were divided into four distinct groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are several evaluations about infraspecific morphological (Talebi et al 2019b), essential oil composition (Salehi et al 2008;Morteza-Semnani et al 2014) and anatomical (Nejadhabibvash et al 2017) variations in S. limbata. On the contrary, we could not find a study on the population genetic diversity and structure of this species in Iran and the world.…”
Section: Introductionmentioning
confidence: 99%